Design and Analysis for a Diving‐Beetle‐Inspired Swimming Robot with Multi‐Flexible Appendages - Xinyi Gao; Zhenlin Jin; Lin Liang; Zhipeng Hu; Kai He; Fengran Xie; Qiyang Zuo (Advanced Intelligent Systems, 2025)
In nature, the diving beetle is a drag‐powered excellent swimmer. It uses the flexible multi‐segment appendages to generate asymmetric force during the power stroke and recovery stroke for swimming. Meanwhile, the middle appendages are considered to help regulate stability. Inspired by this, a comprehensive study on a diving‐beetle‐like swimming robot is presented. The design of the robot is first demonstrated. Soft rubber is used as a passive flexible joint for the multi‐flexible appendage, and the swimming gaits are mimicked. Next, to validate the effectiveness of the proposed appendage design, its dynamic model is established and the effects of overly high and overly low stiffness on net thrust generation are compared. Finally, extensive thrust and swimming tests are conducted. The experimental results show that by mimicking the diving beetle's appendage structure and swimming gaits, the proposed robot can effectively perform forward swimming and turning maneuvers. Furthermore, comparing only the hind appendage, the experimental results reveal that coordinating the hind appendage and the middle appendage gives the robot a faster turning speed. Additionally, utilizing the enhanced maneuverability, a proportional‐derivative controller is employed to control the robot's yaw stability, and the experimental results demonstrate that the robot has good robustness and disturbance resistance.